Analisis Desain Central Body Undercarriage Alat Peraga Mini Excavator Zhugimada dengan Metode Elemen Hingga - Prihadianto, Braam Delfian; Prayitno, Yosephus Ardean Kurnianto; Hasan, Dani Anggoro; Hidayat, Anisa Nurul; Adhim, Inn Aka La’ala Khuluqin (Infotekmesin, 2026)
The availability of practical facilities in mechanical engineering vocational education requires representative yet economical learning media. The development of a mini excavator demonstration tool by the Mechanical Engineering Department of Sekolah Vokasi Universitas Gadjah Mada (SV-UGM) is an effective alternative to support practical and research activities because it reflects the function and mechanism of an excavator with efficient costs and dimensions. This study analyzes the central body undercarriage design of the Zhuigimada mini excavator demonstration tool using the finite element method with the aid of Computer Aided Engineering tools. The material used is American Society for Testing and Materials (ASTM) A572 with a load of 19,620 N. The simulation results show a maximum von Mises stress of 21.69 MPa, a total displacement of 0.0133 mm, and a safety factor of 15.9. These values ​​indicate that the undercarriage design has good strength and stiffness against static loads produces an undercarriage design that is safe, efficient, and representative of the excavator work system.